A novel luminol-based chemiluminescence method for the determination of amikacin sulfate in serum by using trivalent copper-periodate complex - Yu-Fei Hu; Gong-Ke Li; Zhu-Jun Zhang (Elsevier, 2013)
A novel chemiluminescence (CL) reaction was based on the oxidizing reaction of luminol by the trivalent copper-periodate complex (K5[Cu(HIO6)2], DPC) in alkaline medium. The CL intensity could be enhanced in the presence of amikacin sulfate (AKS). A new CL method was developed for the determination of AKS by coupling with flow injection (FI) technology. Because of the distinctive oxidative effect of DPC, the luminol-based CL reaction could occur at a low concentration of 10â7M. The relative CL intensity was proportional to the concentration of AKS in the range of 4.0Ã10â9â4.0Ã10â6g/mL with the detection limit of 1.2Ã10â9g/mL. The relative standard deviation was 2.1% for 8.0Ã10â9g/mL AKS (n=9). The proposed method was successfully applied to the direct determination of AKS at the level of ng/mL in serum samples. The recovery varied from 97.0% to 106.3%. A possible mechanism of the CL reaction was discussed in detail by relating to the CL kinetic characteristics and electrochemical activities of the oxidant DPC. Keywords: Amikacin sulfate, Chemiluminescence, K5[Cu(HIO6)2], Flow injection, Serum sample